A new black fly species of Simulium (Simulium) (Diptera: Simuliidae) from Taiwan - Takaoka, Hiroyuki; Huang, Yao-Te (Zootaxa, 2018)
A new black fly species, Simulium taichungense, is described on the basis of one female, one male and two pupal exuviae from Taiwan. This new species is placed in the S. crocinum species-group of Simulium (Simulium) (Diptera: Simuliidae). It is characterized by the pupal gill with six unpigmented short filaments and pupal abdomen with distinct spine-combs on the dorsal surface of segments 7–9, by which it is easily distinguished from most species in the S. crocinum species-group including two species from Taiwan: Simulium serenum Huang & Takaoka and S. ufengense Takaoka. It is the third species of the S. crocinum species-group from Taiwan. In addition, the male of S. serenum is described for the first time, and intraspecific variations in a few features of the male of S. chungi Takaoka & Huang of the S. chungi species-group are noted.